Gestalt Counseling with Dialog Game Techniques and Hipno Counseling Techniques for Self Achievement - Wayan Eka Paramartha; I Ketut Dharsana; Ni Ketut Suarni (Bisma The Journal of Counseling, 2017)
The purpose of this research is to know the influence between gestalt counseling with techniques of game dialogue and hipnocounseling technique against self achievement in terms of the gender of the student. The research is the research experiments with 2 x 2 factorial design, this research was conducted in SMA Negeri 1 Sukasada. The Sampling technique used to determine the research sample is Random sampling. Data collection methods used are observation, interview, questionnaire and diary, recording documents. Data research results are analyzed using two lines of Anova. The results showed that, there may be differences between the influence of gestalt counseling with techniques of game dialogue and hipnocounseling technique against self achievement.